2021
DOI: 10.1063/5.0045204
|View full text |Cite
|
Sign up to set email alerts
|

The scales of the leading-edge separation bubble

Abstract: The scales of the leading-edge separation bubble

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
(57 reference statements)
4
6
0
Order By: Relevance
“…For example, on plane D at , the streamwise velocity of the LEVs is, on average, . This is in agreement with the findings of Siala and Liburdy (2019), Ōtomo, Henne, Mulleners, Ramesh, and Viola (2020) and Smith et al. (2021), who found that the LEV convects downstream at approximately the mean shear layer velocity.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…For example, on plane D at , the streamwise velocity of the LEVs is, on average, . This is in agreement with the findings of Siala and Liburdy (2019), Ōtomo, Henne, Mulleners, Ramesh, and Viola (2020) and Smith et al. (2021), who found that the LEV convects downstream at approximately the mean shear layer velocity.…”
Section: Resultssupporting
confidence: 89%
“…For example, on plane D at 𝜂 = 0 • , the streamwise velocity of the LEVs is, on average, 0.53U ∞ . This is in agreement with the findings of Siala and Liburdy (2019), Ōtomo, Henne, Mulleners, Ramesh, and Viola (2020) and Smith et al (2021), who found that the LEV convects downstream at approximately the mean shear layer velocity. In fact, assuming that the external shear layer velocity is approximately U ∞ , and the internal flow is approximately stagnant, the mean shear layer velocity is U ∞ /2.…”
Section: E8-11supporting
confidence: 93%
See 1 more Smart Citation
“…For small α, Kutta-Joukowski theory for thin airfoils predicts that the centre of lift is a constant independent of α and is located at a point one quarter of the chord length ahead of the CoV (Anderson 2010). We thus include a constant term as well as one that quadratically decreases with α, the latter yielding a better fit to our experimental measurements and which may reflect the pressure redistribution due to flow reattachment on the upper surface of the plate at low α (Smith, Pisetta & Viola 2021). At larger α for which fully separated flow can be expected, free streamline theory predicts that the centre of pressure moves towards the middle of the plate as α → π/2 and does so approximately linearly (Wu 1955;Lamb 1993;Sefat & Fernandes 2011).…”
Section: Aerodynamic Coefficients and Parameters In The Modelmentioning
confidence: 99%
“…Flow separation on lifting surfaces such as wings, fins, and blades, is often an undesirable phenomena that occurs when the boundary layer of a fluid flowing over a solid surface loses momentum due to an adverse pressure gradient and hence, the streamlines no longer follow the solid contour [1]. When laminar to turbulent transition occurs, at moderate Reynolds numbers, the flow reattaches after separation, forming a short laminar separation bubble (LSB) on the suction side of the foil [2][3][4][5]. Contrarily, if the adverse pressure gradient is too high such as at a high angle of attack, the flow remains separated [6,7].…”
Section: Introductionmentioning
confidence: 99%